Zipper repair of 3 cm iatrogenic colonic perforation with dual‐channel endoscope and twin grasper‐assisted titanium clip - Wei Yang; Wei Wen; Xiaoli Ren; Qi Zhai; Shupei Li; Ji Xuan (DEN Open)
Abstract A 53‐year‐old man undergoing painless colonoscopy for long‐term diarrhea. After colonoscopy withdrawing to the sigmoid colon, a local perforation was found, about 3 cm in size, oval in shape. We used a two‐channel endoscope and grip to pull the edges of the intestinal wall on both sides of the perforation site to close together, and then repair the 3 cm oval perforation of the colon through multiple ordinary titanium clips. The patient had no obvious infection after surgery and recovered well after 1 month of follow‐up. Preliminary experience has shown that using multiple titanium clips under dual‐channel endoscope to zipper suture can effectively repair 3 cm iatrogenic colonic perforations.